Medication and Lifestyle Modification Adherence to Blood Pressure Control Among Hypertensive Patients: A Cross-Sectional Study - Abdul Qodir; Dwi Soelistyoningsih; Wira Daramatasia (Journal of Ners and Midwifery, 2025)
Adherence to medication is a crucial aspect in blood pressure control, which in turn leads to a reduction in the incidence of cardiovascular disease and medical costs. The aim of the study was to determine medication and lifestyle modifications adherence to blood pressure control among hypertensive patients in a public health center. The method of the study used a cross-sectional involving participants with primary hypertension at the Community Health Centre. One hundred respondents were recruited through consecutive sampling methods. Hypertensive patients aged 40 to 74 years who has been taking antihypertensive drugs for at least two months were approved, while hypertensive patients with cormobid and patients with communicative or behavioral impairments were excluded. The instruments used was the TAQPH, which consists of six factors: medication, diet, stimulus, weight control, physical exercise, and stress management. Blood pressure measurements were conducted using a mercury sphygmomanometer. The data was examined with the chi-squared statistical test. Twenty-five (75%) of the patients who demonstrated high levels of adherence had controlled blood pressure. In contrast, 24 (75.0%) patients with medium adherence and 29 (82.9%) patients with low adherence demonstrated uncontrolled blood pressure. A significant correlation was observed between the level of therapy adherence and blood pressure in hypertensive patients (p = 0.001). Patients with low to moderate levels of adherence have uncontrolled blood pressure, whereas those with high levels of adherence have controlled blood pressure.